Nickel Smelter Moratorium: Efforts to Establish Laws to Ensure Legal Certainty of Investment - Silalahi, Firman; Jesica, Kenny (Acta Law Journal, 2024)
The downstream effort is not solely an economic motive, but there are efforts to pursue the target of net zero emissions through the development of Electric Vehicles (EV). Therefore, in the future the transportation sector will shift to the EV ecosystem. Support for the EV ecosystem requires components such as batteries whose the raw materials come from nickel ore produced using hydrometrological methods. This research uses a normative legal research method (legal research) which combines secondary materials in the form of supporting data on the application of Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining in Indonesia. In this research, the authors concludes that the increase in investment of nickel downstream projects has raised concerns about the amount of Indonesian nickel reserves, so the government should planning a moratorium on RKEF type smelters and switching to HPAL smelters. To ensure legal certainty, the government must form regulations aimed at complying with mechanisms and procedures that are in accordance with state administration and capital investment.